Respuesta :

Answer:

[tex]\huge\purple {\boxed {m\angle FEG =23\degree}} [/tex]

[tex] \huge \orange {\boxed {m\angle FEH=113\degree}} [/tex]

Step-by-step explanation:

In the given circle, [tex] \overline{EG} [/tex] is diameter and [tex] \overline{EH} [/tex] is tangent at point E.

[tex]\therefore \widehat {EFG} [/tex] is a semicircular arc.

Since, measure of semicircular arc is 180°

[tex]\therefore m(\widehat {EFG})=180\degree... (1)[/tex]

[tex]\because m( \widehat {EF}) +m(\widehat {FG}) = m(\widehat {EFG}) [/tex] .... (2)

From equations (1) & (2)

[tex]\therefore 134\degree +m(\widehat {FG}) = 180\degree[/tex]

[tex]\therefore m(\widehat {FG}) = 180\degree-134\degree [/tex]

[tex]\therefore m(\widehat {FG}) = 46\degree [/tex]

By inscribed angle theorem:

[tex] m\angle FEG =\frac{1}{2} m(\widehat {FG} ) [/tex]

[tex] m\angle FEG =\frac{1}{2} \times 46\degree [/tex]

[tex]\huge\purple {\boxed {m\angle FEG =23\degree}} [/tex]

By tangent secant theorem:

[tex] m\angle FEH=\frac{1}{2} (46\degree +180\degree) [/tex]

[tex] m\angle FEH=\frac{1}{2} (226\degree) [/tex]

[tex] \huge \orange {\boxed {m\angle FEH=113\degree}} [/tex]

ACCESS MORE